Reverse Cast Metallic Core Based on the Original Prosthetic Crown - Eliana de Souza Bastos Mazuqueli Pereira; Fernando Accetturi; Rachel Gomes Eleutério; Daniela Vieira Buchaim; Rogério Leone Buchaim; Juliana Trindade Clemente-Napimoga (Case Reports in Dentistry)
The dental crown can be restored using the root in clinical situations where the dental remnant allows adequate anchorage by the use of an intraradicular retainer. After endodontic treatment, reconstruction of the dental anatomy depends on correct planning and the type of restoration to be used. This requires reestablishment of form and function with creation of anchoring features, avoiding detachment and favoring the distribution of forces, thus preventing fracture of the remnant due to functional and parafunctional forces applied on the tooth. This paper reports the clinical case of a patient who sought dental care for a full metal-ceramic crown with a cast metallic core with reduced length that had been detached from tooth 24. After clinical and radiographic examination, root integrity was verified. The patient was offered reconstruction with a cast metallic core of satisfactory length, providing adequate retention and support, with reutilization of the original prosthetic crown, serving as a reverse template of the coronal portion of this new core, providing reduction in costs and operational time.